Cancer Metastases from Lung Adenocarcinoma Disappeared After Molecular Targeted Therapy: A Successfully Clinical Treatment Experience - Li MJ; Wei J; Ai GP; Liu Y; Zhu J (Dove Medical Press, 2022)
Meng-Jie Li,1,* Jun Wei,2,* Guo-Ping Ai,3,* Ying Liu,4 Jian Zhu4 1Department of Respiratory Oncology, Renmin Hospital of Qingxian, Cangzhou, 062650, People's Republic of China; 2Department of the First Surgery, Wuhan Jin-Yin-Tan Hospital, Wuhan, 430011, People's Republic of China; 3Department of Radiology, General Hospital of Central Theater Command of the People's Liberation Army, Wuhan, 430070, People's Republic of China; 4Department of Thoracic Cardiovascular Surgery, General Hospital of Central Theater Command of the People's Liberation Army, Wuhan, 430070, People's Republic of China*These authors contributed equally to this workCorrespondence: Jian Zhu; Ying Liu, Department of Thoracic Cardiovascular Surgery, General Hospital of Central Theater Command of the People's Liberation Army, Wuhan, 430070, People's Republic of China, Tel +86-13871166489, Fax +86-27-50772388, Email zhujian0718@163.com; xxwkly@163.comIntroduction: Molecular targeted therapy has shown certain therapeutic effects on various cancer types, especially lung cancer. Here, we report a case of a patient with unresectable non-small cell lung cancer (NSCLC) with bone metastases and metastatic lesions that disappeared after molecular targeted therapy.Patient Information: A 49-year-old male patient's chest CT scan showed a patchy, slightly high-density shadow on the upper lobe of the left lung with an unclear boundary. The multiple thoracic vertebrae, 4th lumbar vertebrae, multiple ribs, right sacroiliac joint, right hip joint, right inferior ramus of pubis, left middle and upper femur, and right proximal radial bone showed nodular and slightly high-density shadows.Interventions: The patient was not considered eligible for tumor resection due to his metastatic lesions. A resected lymph node biopsy was performed. The pathologic findings suggested lung adenocarcinoma, and the gene detection results indicated NM-005228:exon19:c.2235- 2249del:p. GLu746-Ala750del (15.31%), NM-005228:exon20:c. G2356A: p. V786M (1.67%). The patient received the icotinib hydrochloride molecular targeted therapy.Outcomes: After two months of treatment, pulmonary nodules were basically absent on chest CT scan re-examination. After nine months of treatment, no obvious abnormalities in the thoracic vertebral bone were found on 99mTc-MDP bone scan and CT scan re-examination. No obvious structural abnormalities, such as enlarged lymph nodes, could be found by ultrasound re-examination, and the patient remained alive without recurrence at the five-year follow-up.Conclusion: This case report may provide a clue for the future development of molecular targeted therapy for lung cancer. It will allow surgeons to collaborate with oncologists and raise awareness of the benefit of the multidisciplinary approach to the diagnosis and treatment of cancer. Moreover, our results will help patients to fully understand the effect of nonsurgical treatments and improve confidence in the diagnosis and treatment of advanced lung cancer.Keywords: bone metastases, lung cancer, molecular targeted therapy, gene therapy